A Possible Physiological Basis for the Discontinuity of Consciousness - Brennan, Barry J.; Pockett, Susan; Bold, Gary E.; Holmes, Mark D. (Frontiers in Psychology, 2011)
A comparison is made between the frequency of local minima in the analytic power of intracranial EEG (ECoG) from waking and unconscious human subjects and the frequency of putative frames of consciousness reported in earlier psychological literature. In ECoG from unconscious subjects, the frequency of deep minima in analytic power is found to be a linear function of bandwidth. In contrast, in ECoG from conscious subjects, the bandwidth/minima-frequency curve saturates or plateaus at minima frequencies similar to the frequencies of previously reported frames of consicousness. This result is consistent with the hypothesis that local minima in analytic power may act as the shutter in a cinematographic model of consciousness. The fact that artificially generated samples of black noise with power spectra similar to ECoG data give similar results in the analyses above suggests that the discontinuous nature of consciousness is not due to some specifically biological factor, but is simply a consequence of the physical properties of the 1/f (aka power law) oscillations that are widely found in nature.